Obstetric violence - Exter, André den (Medicine, law & society, 2024)
According to a recent Court ruling, Argentina has to take necessary action to prevent maternal death, including a campaign to inform women about their rights during pregnancy, childbirth and the post-partum care period, broadcasted on radio and television and available at all maternity clinics in the country. The court’s message is crystal clear: countries in America should take the problem of obstetric violence seriously. But what about European countries? It is argued that the message also affects reproductive policies in European countries.
Keywords: ECtHR; human rights; IAHRCt; obstetric violence; reproductive health